A chronicle of echoes : who's who in the implosion of American public education - Schneider, Mercedes K. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
"Corporate reform" is not reform at all. Instead, it is the systematic destruction of the foundational American institution of public education. The primary motivation behind this destruction is greed. Public education in America is worth almost a trillion dollars a year. Whereas American public education is a democratic institution, its destruction is being choreographed by a few wealthy, well-positioned individuals and organizations. This book investigates and exposes the handful of people and institutions that are often working together to become the driving force behind destroying the community public school.